(untitled) (Educational Dimension, 2024)
This article attempts to analyse the definition and structure of the concept of "intercultural competence" in scientific research and normative documents at the Ukrainian and European levels, to identify commonalities and differences, to characterise positive changes and, based on the analysis, to formulate a definition of the concept that would reflect today’s realities and take into account modern challenges in education (general, foreign language). Starting from the end of the 20th century, scientific works of English-speaking, German-speaking, and domestic scientists were studied, but the main focus was on research from the last 20 years due to significant changes in the structure of societies due to globalisation, migration processes, and the activation of contacts in the professional and private spheres of representatives of different linguistic and cultural communities. Attention is drawn to the fact that understanding the concept of "intercultural competence" acquired new meanings at different stages of its research. Among the reasons for reconsideration and clarification are primarily the challenges that appeared under the influence of social processes in the pan-European and world dimensions, taking into account the national characteristics of countries’ development. In accordance with the shift in emphasis in the definition of the concept, its structure also changed; however, despite the selection of specific components by different authors, the structure of intercultural competence retained a common core and layered new components. In the educational discourse, there is a noticeable increase in attention to the concept in the context of social competence, the development of which is aimed, among other things, at conflict-free coexistence, successful communication, and the ability to adapt to a multilingual and multicultural society.